Plaque Psoriasis Successfully Treated with an Individualised Homoeopathic Medicine Lycopodium: A Case Report - Kanwar, Annu; Ram, Hanuman; Kumar, Narender; Bagdi, Navita (Homœopathic Links, 2020)
Introduction Psoriasis is an immune-mediated disease affecting the skin and joints with a prevalence of 0.44 to 2.8% in India. This manifests most often as plaque psoriasis (PP); it is a chronic, relapsing, inflammatory skin disorder with a strong genetic basis. PP is rarely life threatening but it is often intractable to treatment. Here, a 31-year-old male diagnosed with PP presented with a history of multiple reddish moist lesions with thickness and scaling of skin from right forearm, chest, abdomen and back for 3 years. Patient was taking allopathic medications for the same but there was only temporary relief of the complaints. So, patient approached for homeopathic intervention for permanent cure. On the basis of the totality of symptoms and analysis by repertorisation, homoeopathic medicine Lycopodium was prescribed and repetition was done according to the response of medicine and as per the condition of patient, following the principles of homoeopathy. It showed improvement in all complaints, but there was relapse of eruptions after sometime which called for increase in the potency of the Lycopodium (200C & 1M) as per homoeopathic principles. The assessment of patient was done on the basis of Psoriasis Area and Severity Index (PASI) score and photographic evidence. The PASI score of the patient at baseline was 23.4 and it was reduced to 1 after the continuous follow-up of patient for 1 year. Photographs during follow-up visits have provided a documentary evidence about the effectiveness of homoeopathic medicine Lycopodium in plaque psoriasis. Thus, it can be concluded that homoeopathy plays an effective role in managing the cases of PP symptomatically along with complete recovery of the patient.
Keywords: individualised homoeopathic medicine; Lycopodium; PASI score; plaque psoriasis (PP)